Maltose transport in Escherichia coli K-12: involvement of the bacteriophage lambda receptor. - Szmelcman, S (1975)
Mutants affected in lamB, the structural gene for phage lambda receptor, are unable to utilize maltose when it is present at low concentrations (less than or equal 10 muM). During growth in a chemostat at limiting maltose concentrations, the lamB mutants tested were selected against in the presence of the wild-type strain. Transport studies demonstrate that most lamB mutants have deficient maltose transport capacities at low maltose concentrations. When antibodies against purified phage lambda receptor are added to a wild-type strain, transport of maltose at low concentrations is significantly reduced. These results strongly suggest that the phage lambda receptor molecule is involved in maltose transport.